Quasi‐Solid‐State Aluminum–Air Batteries with Ultra‐high Energy Density and Uniform Aluminum Stripping Behavior - Chaonan Lv; Yixin Li; Yuanxin Zhu; Yuxin Zhang; Jialin Kuang; Qing Zhao; Yougen Tang; Haiyan Wang (Advanced Science, 2023)
Abstract Aqueous aluminum–air batteries are attracting considerable attention with high theoretical capacity, low‐cost and high safety. However, lifespan and safety of the battery are still limited by the inevitable hydrogen evolution reaction on the metal aluminum anode and electrolyte leakage. Herein, for the first time, a clay‐based quasi‐solid‐state electrolyte is proposed to address such issues, which has excellent compatibility and a liquid‐like ionic conductivity. The clay with uniform pore channels facilitates aluminum ions uniform stripping and reduces the activity of free H2O molecules by reconstructing hydrogen bonds network, thus suppressing the self‐corrosion of aluminum anode. As a result, the fabricated aluminum–air battery achieves the highest energy density of 4.56 KWh kg−1 with liquid‐like operating voltage of 1.65 V and outstanding specific capacity of 2765 mAh g−1, superior to those reported aluminum–air batteries. The principle of constructing quasi‐solid‐state electrolyte using low‐cost clay may further promote the commercialization of aluminum–air batteries and provide a new insight into electrolyte design for aqueous energy storage system.